Management outcome of premature rupture of membranes in a tertiary facility in South Western Nigeria. Annals Ibadan (2021)
Background: Pre-labour rupture of membranes (PROM) contributes immensely to the potential risk of maternal morbidity and mortality. Objective: To explore the incidence and management outcome of PROM at Ladoke Akintola University of Technology Teaching Hospital (LTH), Ogbomoso, Nigeria Methods: A retrospective study of 61 cases of PROM managed at LTH, Ogbomoso over a 3-year period. Information on the socio-demographics and obstetrics characteristics, management instituted, and outcomes were obtained using a structured proforma. Data were analysed using SPSS version 20. Level of significance was set at <0.05 and 95% confidence interval. Results: The incidence of PROM was 4.1% with a perinatal mortality rate of 0.18 per 1000 deliveries. Twenty (33%) were pre-term while 41 (67%) were term PROM with 10% of the perinatal death occurring among those with preterm PROM. The mean age of the women was 36.9 (SD=2.1) years and median parity of 1(range 1-5) children. There was a significant association between the women’s gestational age at which PROM occurred with the latency period (p< 0.001). Fetal birth weight, apgar score and neonatal intensive care unit (NICU) admission were all significantly associated with the gestational age at which PROM occurred (p<0.05). There was a significant difference between the intervention instituted and mode of delivery (p=0.009). Conclusion: The incidence of PROM at term was high and conservative/ expectant management was effective. The latency period and fetal outcomes such as birth weight, apgar score and NICU admission were determined by the gestational age at which PROM occurred.